Automatic Financial Report Application - L Ismawati; T H A Simon; S U Kamisa; M A N Shidiq; N P Dewi (Peneliti.net, 2021)
Financial reports are important for business activity. From these financial reports, we can see transactions that are carried out at any time. Besides, it can be easier to calculate finances. Business actors' current condition is still carrying out their financial records manually, causing delays in financial recording and not to mention if the transaction evidence records are lost or damaged. The purpose of designing this application is to create a new application that can be used to record financial reports related to trading activities. We used a descriptive research method because we need to do some surveys to conclude the mistake. This research is an automatic financial reporting application design that we will create based on the results of the survey we have conducted. When compiling the design, we will make some forms for the transaction that will appear at the beginning of the application. After filling in the transaction forms, they will inputs automatically into the balance sheet and income statement.